A Genomic Analysis of Rat Proteases and Protease Inhibitors - Puente, Xose S.; López-Otín, Carlos (Genome Research, 2004)
Proteases perform important roles in multiple biological and pathological processes. The availability of the rat genome sequence has facilitated the analysis of the complete protease repertoire or degradome of this model organism. The rat degradome consists of at least 626 proteases and homologs, which are distributed into 24 aspartic, 160 cysteine, 192 metallo, 221 serine, and 29 threonine proteases. This distribution is similar to that of the mouse degradome but is more complex than that of the human degradome composed of 561 proteases and homologs. This increased complexity of rat proteases mainly derives from the expansion of several families, including placental cathepsins, testases, kallikreins, and hematopoietic serine proteases, involved in reproductive or immunological functions. These protease families have also evolved differently in rat and mouse and may contribute to explain some functional differences between these closely related species. Likewise, genomic analysis of rat protease inhibitors has shown some differences with mouse protease inhibitors and the expansion of families of cysteine and serine protease inhibitors in rodents with respect to human. These comparative analyses may provide new views on the functional diversity of proteases and inhibitors and contribute to the development of innovative strategies for treating proteolysis diseases.
10.1101/gr.1946304